Connecting Leadership and Learning: Do Versatile Learners make Connective Leaders? - Jill L. Robinson (Laureate Education Inc, 2016)
Abstract Recent failures in leadership, suggest that creating better-quality leadership development programs is critical. In moving from theory to practice, this paper examined the relationship between learning style and leadership style which may enable us to move away from one-size-fits-all leadership development programs. Utilizing Kolb's Experiential Learning Model and Connective Leadership theory, approximately 3600 college students were analyzed to discover whether versatility in learning styles translates into versatility in leadership styles. One group of versatile learners reported using a wider range of leadership styles suggesting that learning flexibility may transfer to leadership flexibility. Surprisingly, learners of all types reported utilizing Power and Intrinsic styles of leadership above all others. Implications for leadership development include considering individual differences when crafting leadership programs, matching learning styles to leader training, and the need to move beyond one set of leadership behaviors to increase flexibility in dealing with complex situations. Using a large sample rarely seen in management studies, this paper makes key contributions to the literature.